2020
DOI: 10.1016/j.envpol.2020.114797
|View full text |Cite
|
Sign up to set email alerts
|

A new route for manufacturing poly(aminophosphonic)-functionalized poly(glycidyl methacrylate)-magnetic nanocomposite - Application to uranium sorption from ore leachate

Abstract: A high-energy ball milling of magnetite nanoparticles with amino-phosphonic functionalized poly(glycidyl methacrylate) polymer is used for manufacturing a highly efficient magnetic sorbent for U(VI) sorption from aqueous solutions. The Uranyl ions were adsorbed through the binding with amine and phosphonic groups as confirmed by Fourier Transform infrared (FTIR) and X-ray photoelectron spectroscopy (XPS) analyses. The maximum sorption capacity (up to 270 mg U g À1) occurred at pH ¼ 3e4; Langmuir isotherm well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 70 publications
4
20
0
Order By: Relevance
“…Additionally, P2-APEI holds phosphonate moieties with pK a values supposed to be much higher [55], depending on the substituting groups on the phosphonate entity. The order of magnitude of the pH PZC is consistent with the value reported for polyaminophosphonic acid-functionalized poly(glycidyl methacrylate) (i.e., 2.69) [28] and a composite obtained by high-energy ball milling of magnetite with aminophosphonic derivative of PGMA (i.e., 2.83) [56]. The functionalized sorbent will be deprotonated on a wider pH range than the raw material: the repulsion of metal cations is expected to be decreased for P2-APEI in weakly acidic solutions.…”
Section: Elemental Analysis and Ph Pzcsupporting
confidence: 87%
“…Additionally, P2-APEI holds phosphonate moieties with pK a values supposed to be much higher [55], depending on the substituting groups on the phosphonate entity. The order of magnitude of the pH PZC is consistent with the value reported for polyaminophosphonic acid-functionalized poly(glycidyl methacrylate) (i.e., 2.69) [28] and a composite obtained by high-energy ball milling of magnetite with aminophosphonic derivative of PGMA (i.e., 2.83) [56]. The functionalized sorbent will be deprotonated on a wider pH range than the raw material: the repulsion of metal cations is expected to be decreased for P2-APEI in weakly acidic solutions.…”
Section: Elemental Analysis and Ph Pzcsupporting
confidence: 87%
“…Actually, the effective binding mechanisms may be a contribution of these different mechanisms whose relative and respective importance depends on experimental conditions. In the case of uranyl binding on magnetic polyglycidylmethacrylate functionalized with aminophosphonic groups, Galhoum et al [74] reported the strong interaction of uranyl species with several functional groups (based on FTIR and XPS analyses). A tetradentate complex is formed by ionic bond with a deprotonated oxygen atom of phosphonate moiety, the coordinate bonding with 2 nitrogen donors of amine groups and the coordination with one oxygen donor of OH group.…”
Section: Tablementioning
confidence: 99%
“…Uranium having a great affinity for amine [29][30][31], phosphonic [26,32,33] and amidoxime groups [34][35][36], many resins have been designed by the grafting of these reactive groups on synthetic resins [37] but also on biopolymer-based supports [38,39]. In the current work, magnetic/chitosan nanoparticles decorated with glycidylmethacrylate (GMA) have been functionalized with amine groups (diethylenetriamine, DETA) to prepare GMA-magnetic/chitosan-amine sorbent (R-Amine).…”
Section: Synthesis Of Magnetic Chitosan/gma Compositementioning
confidence: 99%